PENERAPAN MATERI PEMBELAJARAN MENYIMAK BERDASARKAN KURIKULUM MERDEKA MENGGUNAKAN CERITA RAKYAT YANG BERJUDUL “SI PAHIT LIDAH” DALAM PROSES PEMBELAJARAN TINGKAT SMA: THE IMPLEMENTATION OF LEARNING MATERIALS BASED ON THE INDEPENDENCE CURRICULUM USING FOLKLORE STORIES TITLE “SI PAHIT LIDAH” IN THE LEARNING PROCESS OF HIGH SCHOOL LEVEL - Siti Salamah (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2023)
ABSTRACT Listening activity is a skill that needs to be achieved in the Independent Curriculum in the Senior High School (SMA) education unit. One of the achievements of the listening element aims to enable students to have listening skills which include analyzing and interpreting information from various types of audio-visual (fictional or non-fiction) and aural texts, as well as reviewing and testing the topic information heard based on facts. This study aims to analyze the role of story-based learning materials "Si Pahit Lidah" ​​on the listening skills of high school students. This study uses the method used is qualitative accompanied by descriptive analytical methods. Producing the values ​​contained in the story "Si Pahit Lidah" ​​in the form of moral values, educational values, religious values, and cultural values ​​as well as the role of stimulating listening motivation, increasing the ability to analyze and interpret information, develop information exploration abilities, and improve evaluation abilities. Key Words : Listening, Folklore, Freedom Curriculum.